Evaluation of Power System Reliability Considering Direct Load Control Effects - Ali Mansouri; Ali Aazami; Amin Omidian; Ehsan Mohamadian; Rahmat Aazami (International Journal of Electrical and Computer Engineering (IJECE), 2013)
With the development of deregulated power systems and increase of prices in some hours of day, demand side management programs were noticed more by customers. In restructured power systems, DSM programs are introduced as DEMAND RESPONSE. In this paper we try to evaluate the effect of DR programs on power system reliability and nodal reliability. In order to reach to this target, Direct Load Control program, as the most common demand response program, is considered. Effects of demand response programs on system and nodal reliability of a deregulated power system are investigated using direct load control and economic load model, DC power-flow-based optimal load curtailment objective and reliability evaluation techniques. The proposed method is evaluated by numerical studies based on a small reliability test system (RBTS), and simulation results show that demand response program can improve the system and nodal reliability.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2295